Content Marketing, e-WOM, dan Brand Image Pengaruhnya terhadap Minat Beli Tucicakes - Gusti Ayu Putu Rani Lokahita; I Ketut Selamet; I Putu Iwan Pramana Putra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The digitalization era has shifted the role of social media to become a central axis in contemporary marketing practices. Social media no longer merely functions as a communication channel, but has become a strategic space that shapes public perceptions, interests, and consumption tendencies. This study aims to examine the extent to which content marketing, electronic word of mouth (e-WOM), and brand image influence consumer purchasing interest in Tucicakes products. The study subjects involved residents of South Denpasar aged at least 17 years who had been exposed to Tucicakes promotional content on social media and had purchasing experience. A total of 102 respondents were analyzed using a quantitative approach. Data processing was carried out through validity and reliability tests, classical assumptions, multiple linear regression analysis, and hypothesis testing with the F test and t test assisted by SPSS version 26. The research findings confirmed that these three variables have a positive and significant influence on purchasing interest, both simultaneously and partially.